Solitary Wave Solutions of the (3+1)-dimensional Khokhlov–Zabolotskaya– Kuznetsov Equation by Using the (G?/G, 1/G)-Expansion Method - Durur, Hülya; Duran, Serbay; Yokuş, Asif (Adiyaman University, 2021)
In this study, the (3+1)-dimensional Khokhlov-Zabolotskaya-Kuznetsov (KZK) equation, which is a mathematical model of non-absorption and dispersion in the non-linear medium, which sheds light on the sound beam phenomenon, which has a physically important place, is examined. In order to find the exact solution of this equation, an effective and reliable method, (G!/G, 1/G)-expansion method, is used among analytical methods. The purpose of this method is to obtain more than one traveling wave solution classes depending on the conditions of the ? parameter. These classes are categorized into hyperbolic, trigonometric, complex trigonometric and rational forms. The graphics of the solitary waves represented by these successfully obtained solution classes are presented as 2-dimensional, 3-dimensional and contours. This article makes use of ready-made package programs for complex arithmetic operations and graphic drawings. © 2021, Adiyaman University. All rights reserved.
(3+1)-Boyutlu Khokhlov–Zabolotskaya–Kuznetsov Denkleminin (G?/G, 1/G)-Açılım Metodu Yardımıyla Solitary Dalga Çözümleri
Keywords: (G?/G, 1/G)-expansion method; (3+1)-dimensional Khokhlov; Kuznetsov equation; Traveling wave solution; Zabolotskaya